Methane Hydrate Formation and Evolution During Sedimentation. Issue 4 (8th April 2021) - You, K.; Flemings, P. B.
Abstract: We explored methane hydrate formation with sedimentation with a newly developed one‐dimensional, multiphase flow, multicomponent transport numerical model. Our model couples methane hydrate formation from in situ microbial methane generation within the hydrate stability zone (HSZ), methane recycling, and microbial methane generation below the base of the hydrate stability zone (BHSZ). Both recycled methane and deeply generated methane are transported into the HSZ by buoyancy‐driven free gas flow. Free gas flows through the HSZ by both the processes of capillary‐dependent pore fillings and by salt exclusion during hydrate formation, with the former being the dominant mechanism. We quantitively illustrated the formation of enriched hydrate in muddy sediments above, and interconnected free gas below, the BHSZ, which are common features along the world's continental margin. In addition, we showed two ways to form concentrated methane hydrate above the BHSZ. The first mechanism is local free gas flow during methane recycling. This happens at sites with sufficient methane generation above the BHSZ. The second mechanism is deep microbial methane generation which is transported into the HSZ by free gas flow. This mechanism plays a more important role at sites with high sedimentation rates. This study provides new insights into methane hydrate formation and distribution below the seafloor. It is important for understanding the carbon cycle and carbon storage below the seafloor and for resource evaluation and exploitation. Plain Language Summary: Methane hydrate is an ice‐like solid composed of methane and water that is found in a cold, high pressure, layer (the HSZ) near the seafloor in the deep ocean. We modeled how methane hydrate forms in nature as sediment is deposited and buried with time. We simulated the generation of methane by bacteria that consume organic carbon and we describe the resultant flow of methane as gas bubbles. Where sediment is buried rapidly, methane is mostly generated below the HSZ and flows upward as gas bubbles due to buoyancy. This brings methane into the HSZ where hydrate forms. At locations where sediment is buried slowly, methane is mostly generated within the HSZ where it is trapped as hydrate in sediments and buried with time. When this hydrate passes below the HSZ, it dissociates and releases gas bubbles. These gas bubbles flow upward, reenter the HSZ, and reform hydrate. Our study suggests that it is most possible to find high‐concentration methane hydrate at topographic highs that can be fed by gas bubble flow, which is important for understanding the carbon cycle and carbon storage below the seafloor and for resource evaluation and exploitation. Key Points: We illuminated methane hydrate formation during sedimentation with a newly developed one‐dimensional numerical model Free gas flow from methane recycling and deep methanogenesis forms concentrated methane hydrate near the base of the hydrate stability zone Deep methanogenesis plays a significant role in forming concentrated methane hydrate at sites with high sedimentation rates